2000
DOI: 10.1021/ie000356j
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Size Selectivity into Synergistic Solvent Extraction:  A Review of Crown Ether-Containing Systems

Abstract: This paper provides a comprehensive review of synergistic solvent extraction using crown ethers with a focus on the role of both extractants in facilitating cation-specific separations. An introduction to the various equilibria affecting synergistic extraction using crown ethers is followed by a review of the work published in this field during the 1972-1999 time period. The influence of various solvent extraction parameters on the potential for cation-selective synergism is critically examined. Those synergis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
127
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 149 publications
1
127
0
Order By: Relevance
“…Note, the similar feature was observed also recently in organic-inorganic composite structure of [18-crown-6][(UO 2 ) (CrO 4 )(H 2 O) 3 ] [25]. Synthesis procedure and knowledge of structural architecture of 2 can be also of practical importance taking into account the known fact that hydrogen peroxide is a product of the radiation-driven radiolysis of water on the one-hand and the application of crown ethers in actinide partitioning on another hand [26].…”
mentioning
confidence: 76%
“…Note, the similar feature was observed also recently in organic-inorganic composite structure of [18-crown-6][(UO 2 ) (CrO 4 )(H 2 O) 3 ] [25]. Synthesis procedure and knowledge of structural architecture of 2 can be also of practical importance taking into account the known fact that hydrogen peroxide is a product of the radiation-driven radiolysis of water on the one-hand and the application of crown ethers in actinide partitioning on another hand [26].…”
mentioning
confidence: 76%
“…Crown ethers possess an inner cavity that exhibits partial selectivity for certain sizes of ions. Since this time, several other structures have been synthesized with various levels of selectivity, as highlighted in a review by Bond in 2000 [74].…”
Section: Crown Ethersmentioning
confidence: 99%
“…It seems that they can bind the majority of the elements of the periodic table [19,20]. And Zhang et al reported that the anti-wear and frictionreduction behaviors of brominobenzene-15-crown-5 were much better than ZDDP, which used as an additive in liquid paraffin [21,22].…”
Section: Introductionmentioning
confidence: 99%